Restorative Justice Dalam Penyelesaian Tindak Pidana Yang Dilakukan Oleh Anak - Arman S (Fakultas Hukum, Universitas Sawerigading Makassar, 2023)
The concept of Restorative Justice as an alternative resolution of juvenile criminal cases. Restorative Justice is interpreted as a process where all parties involved in a particular criminal act sit together to solve problems and think about how to deal with victims and perpetrators of the law, while still prioritizing the principle of the best interests of the child and the punishment process is the last resort without ignoring children's rights. If the legal process continues with the process of reporting to the police, then basically the implementation of the law is through diversion efforts carried out by the police using discretionary authority. Discretion is a transfer from formal criminal court processes to informal processes to be resolved through deliberation. This research uses normative juridical research methods. This normative legal research is carried out in a qualitative descriptive manner, that is, the material or legal materials are collected, sorted for further study and analysis of their content, so that the level of synchronization, suitability of norms and the submission of new normative ideas can be identified. From the results of this research, it is concluded that restorative justice in resolving criminal acts committed by children is very concerned with rebuilding relationships after a criminal act has occurred, rather than exacerbating the rift between the perpetrator, victim and society which is the character of today's modern criminal justice system. Restorative justice is a